Rubber composition and tire
By blending inorganic fiber materials with coupling agents in the rubber composition, the challenges of achieving high fracture strength and anisotropy are addressed, leading to enhanced ride comfort and steering stability in tire internal members.
Patent Information
- Application Number
- JP2025009129
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-11-11
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-10-19
AI Technical Summary
Conventional rubber compositions with fiber materials face challenges in achieving high fracture strength and anisotropy due to poor dispersion of fiber materials within the rubber matrix, leading to decreased fracture strength and inadequate ride comfort and vibration absorption.
A rubber composition is developed by blending inorganic fiber materials with coupling agents, specifically a silane coupling agent, to improve the dispersion and orientation of inorganic fibers within the rubber matrix, thereby enhancing fracture strength and anisotropy.
The rubber composition achieves high levels of fracture strength and anisotropy, resulting in improved ride comfort and steering stability when used in tire internal members.
Smart Images

Figure 2025063269000001 
Figure 2025063269000002 
Figure 2025063269000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition containing an inorganic fiber material and a tire having an inner member made of the rubber composition. [Background technology]
[0002] There is a known technique for imparting anisotropy to the modulus of rubber by blending nanomaterials of biological origin, such as cellulose fiber, into tire components (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5691463 Summary of the Invention [Problem to be solved by the invention]
[0004] It is believed that rubber becomes stronger by forming a network structure, and that fiber materials are more likely to obtain anisotropy. However, if the fiber material is poorly dispersed in the rubber matrix, the fiber material aggregates, making it difficult to obtain anisotropy, and since sufficient reinforcement for the rubber matrix is not obtained, the breaking strength is also thought to decrease. In addition, rubber compositions containing conventional fiber materials have a high elastic modulus, and do not fully satisfy market requirements in terms of ride comfort and vibration.
[0005] An object of the present invention is to provide a rubber composition which achieves both high breaking strength and high anisotropy. [Means for solving the problem]
[0006] As a result of extensive research, the present inventors have found that by compounding an inorganic fiber material and a coupling agent, a rubber composition which achieves both high breaking strength and high anisotropy can be obtained, and have thus completed the present invention.
[0007] That is, the present invention provides [1] A rubber composition containing a rubber component, an inorganic fiber material, and a coupling agent; [2] The rubber composition according to the above [1], wherein the ratio (M100a / M100b) of the 100% modulus M100a in the grain direction to the 100% modulus M100b in the anti-grain direction is 1.10 or more. [3] The rubber composition according to the above [1] or [2], further containing carbon black (preferably 1 to 100 parts by mass, more preferably 5 to 80 parts by mass, per 100 parts by mass of the rubber component). [4] The rubber composition according to any one of the above [1] to [3], further comprising a plasticizer (preferably 1 to 90 parts by mass, more preferably 3 to 70 parts by mass, per 100 parts by mass of the rubber component). [5] The rubber composition according to any one of the above [1] to [4], wherein the rubber component contains an isoprene-based rubber (preferably 5% by mass or more, more preferably 10 to 90% by mass). [6] The rubber composition according to any one of the above [1] to [5], wherein the coupling agent is a silane coupling agent. [7] The rubber composition according to any one of [1] to [6] above, containing 1 to 40 parts by mass of the coupling agent per 100 parts by mass of the rubber component. [8] The rubber composition according to any one of the above [1] to [7], wherein the coupling agent is a silane coupling agent having a sulfide group. [9] Furthermore, the cetyltrimethylammonium bromide adsorption specific surface area (CTAB) is 180m 2 The rubber composition according to any one of the above [1] to [8], containing carbon black in an amount of not more than 1 / g (preferably 1 to 100 parts by mass, more preferably 5 to 80 parts by mass, per 100 parts by mass of the rubber component);
[10] The rubber composition according to any one of the above [1] to [9], wherein the inorganic fiber material is contained in an amount of 1 to 50 parts by mass per 100 parts by mass of the rubber component, and the inorganic fiber material has an average diameter D of 1.0 to 2000 nm, an average length L of 0.10 to 100 μm, and an aspect ratio L / D of 2 to 1000.
[11] The rubber composition according to any one of the above [1] to
[10] , wherein the inorganic fiber material is one or more inorganic fiber materials selected from the group consisting of magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, and sepiolite.
[12] A tire internal member made of the rubber composition according to any one of [1] to
[11] above.
[13] A tire having the tire internal member according to
[12] above.
[14] The tire according to the above
[13] , which is a passenger car tire. Effect of the Invention
[0008] According to the present invention, a rubber composition that achieves both high breaking strength and high anisotropy is provided by blending an inorganic fiber material and a coupling agent. In addition, a tire having an internal tire member made of the rubber composition has a well-balanced improvement in ride comfort and handling stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The rubber composition of the present disclosure contains a rubber component, an inorganic fiber material, and a coupling agent, and therefore exhibits excellent fracture strength and anisotropy.
[0010] Without intending to be bound by theory, the mechanism by which the rubber composition of the present disclosure exhibits excellent fracture strength and anisotropy is believed to be as follows.
[0011] By blending an inorganic fiber material into a rubber composition, it is possible to give the rubber modulus anisotropy, but it is believed that the inorganic fiber material is less likely to disperse in the rubber component than fillers such as carbon black. Therefore, it is believed that the entire rubber matrix cannot be reinforced, making it difficult to obtain sufficient fracture strength and anisotropy. Therefore, by blending a coupling agent together with the inorganic fiber material, the dispersibility of the inorganic fiber material in the rubber matrix is improved, the entire matrix is reinforced, and it is possible to orient the inorganic fiber material in a uniform state, which is believed to improve the anisotropy.
[0012] From the viewpoint of excellent anisotropy, the rubber composition (vulcanized rubber) of the present disclosure has a ratio of 100% modulus M100a in the grain direction to 100% modulus M100b in the anti-grain direction as an index of anisotropy (M100a / M100b, sometimes referred to as "modulus ratio" in this specification) of preferably 1.10 or more, more preferably 1.15 or more, and even more preferably 1.20 or more. On the other hand, the upper limit of the modulus ratio is not particularly limited, but is usually 2.00 or less, and may be 1.80 or less, 1.60 or less, or 1.50 or less. By making the modulus ratio 1.10 or more, it is possible to realize a flexible response in the anti-grain direction of the inorganic fiber material oriented in a highly dispersed state by the coupling agent, and to increase the rigidity in the grain direction and improve the responsiveness. In this specification, "grain direction" means the rolling direction when forming a sheet by extrusion or shearing treatment, and "anti-grain direction" means the direction perpendicular to the grain direction.
[0013] In addition, when the rubber composition is used as a tire, the grain direction of the inorganic fibers may be any of the circumferential direction, radial direction, and width direction of the tire, but from the viewpoint of improving ride comfort and steering stability in a well-balanced manner, it is preferable to arrange the inorganic fibers along the tire circumferential direction. By orienting the inorganic fibers in the tire circumferential direction, a flexible response is realized to the input (vibration) from the tire perpendicular direction during rolling, and by increasing the rigidity in the orientation direction (tire circumferential direction), the responsiveness to the input during steering is improved. It is considered that this leads to a well-balanced improvement in ride comfort and steering stability.
[0014] A procedure for producing a tire, including the production of a rubber composition according to an embodiment of the present disclosure, will be described in detail below. However, the following description is merely an example for explaining the present disclosure, and is not intended to limit the technical scope of the present invention to the described range. In this specification, when a numerical range is indicated using "to" it is intended to include both ends of the numerical range.
[0015] <Rubber component> Examples of rubber components that can be used in the present disclosure include diene rubbers such as isoprene rubber, styrene butadiene rubber (SBR), butadiene rubber (BR), styrene isoprene butadiene rubber (SIBR), chloroprene rubber (CR), and acrylonitrile butadiene rubber (NBR); and non-diene rubbers such as ethylene propylene diene rubber (EPDM), butyl rubber (IIR), and halogenated butyl rubber (X-IIR). These may be used alone or in combination of two or more. The rubber component may be a rubber component containing at least one selected from the group consisting of isoprene-based rubber, SBR, and BR, a rubber component containing an isoprene-based rubber, a rubber component containing an isoprene-based rubber and BR, a rubber component consisting only of an isoprene-based rubber and BR, a rubber component containing BR, a rubber component containing BR and SBR, a rubber component consisting only of BR and SBR, a rubber component containing an isoprene-based rubber, SBR, and BR-isoprene-based rubber, or a rubber component consisting only of an isoprene-based rubber, SBR, and BR.
[0016] The content of the diene rubber in 100% by mass of the rubber component is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 85% by mass or more. The rubber component may be composed only of the diene rubber.
[0017] (Isoprene rubber) As the isoprene-based rubber, for example, isoprene rubber (IR) and natural rubber, which are common in the tire industry, can be used. In addition to unmodified natural rubber (NR), natural rubber also includes modified natural rubber such as epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), deproteinized natural rubber (DPNR), high-purity natural rubber, and grafted natural rubber. These isoprene-based rubbers may be used alone or in combination of two or more.
[0018] The NR is not particularly limited, and any NR commonly used in the tire industry can be used, such as SIR20, RSS#3, and TSR20.
[0019] When an isoprene-based compound is contained, the content in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 20% by mass or more, and particularly preferably 30% by mass or more, from the viewpoint of breaking strength. On the other hand, the upper limit of the content of the isoprene-based compound in the rubber component is not particularly limited, but is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and particularly preferably 75% by mass or less.
[0020] (SBR) The SBR is not particularly limited, and examples thereof include solution-polymerized SBR (S-SBR), emulsion-polymerized SBR (E-SBR), and modified SBRs thereof (modified S-SBR, modified E-SBR), with S-SBR being preferred. The modified SBR includes SBR whose terminals and / or main chains are modified, and modified SBRs (condensates, those having a branched structure, etc.) coupled with tin, silicon compounds, etc. In addition, the SBR includes oil-extended types in which the flexibility is adjusted by adding an extender oil, and non-oil-extended types in which no extender oil is added, and either of these can be used. Examples of the SBR include SBR manufactured and sold by JSR Corporation, Asahi Kasei Chemicals Corporation, Nippon Zeon Corporation, etc. These SBRs may be used alone or in combination of two or more types.
[0021] From the viewpoint of grip performance, the styrene content of SBR is preferably 15% by mass or more, more preferably 18% by mass or more, and even more preferably 20% by mass or more. From the viewpoint of polymer dispersibility and fuel efficiency performance, it is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less. In this specification, the styrene content of SBR is 1 It is calculated by H-NMR measurement.
[0022] When SBR is contained, the content in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, from the viewpoint of abrasion resistance. There is no upper limit to the content of SBR in the rubber component, but it is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and particularly preferably 75% by mass or less.
[0023] (BR) The BR is not particularly limited, and examples of the BR that can be used include those commonly used in the tire industry, such as BR with a cis 1,4 bond content (cis content) of less than 50% (low cis BR), BR with a cis 1,4 bond content of 90% or more (high cis BR), rare earth butadiene rubber (rare earth BR) synthesized using a rare earth catalyst, BR containing syndiotactic polybutadiene crystals (SPB-containing BR), and modified BR (high cis modified BR, low cis modified BR). These BRs may be used alone or in combination of two or more.
[0024] The cis-1,4 bond content of the high-cis BR is preferably 95% or more, more preferably 97% or more. The inclusion of high-cis BR can improve low-temperature properties and wear resistance. Examples of high-cis BR include high-cis BR manufactured and sold by Zeon Corporation, Ube Industries, JSR Corporation, etc. Examples of rare earth-based BR include rare earth-based BR manufactured and sold by Lanxess Corporation, etc.
[0025] The SPB-containing BR is not one in which 1,2-syndiotactic polybutadiene crystals are simply dispersed in the BR, but one in which the 1,2-syndiotactic polybutadiene crystals are dispersed after being chemically bonded to the BR. An example of the SPB-containing BR is the SPB-containing BR manufactured and sold by Ube Industries, Ltd.
[0026] The modified BR may be obtained by polymerizing 1,3-butadiene with a lithium initiator and then adding a tin compound, and the terminals of the modified BR molecule may be bonded with a tin-carbon bond (tin-modified BR), or butadiene rubber having a condensed alkoxysilane compound at the active terminal of the butadiene rubber (modified BR for silica), etc. Examples of such modified BR include tin-modified polymer and S-modified polymer (modified for silica) manufactured by ZS Elastomer Co., Ltd.
[0027] When BR is contained, the content in 100% by mass of the rubber component is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, still more preferably 20% by mass or more, and particularly preferably 25% by mass or more, from the viewpoint of abrasion resistance performance. The upper limit of the content of BR in the rubber component is not particularly limited, but is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and particularly preferably 75% by mass or less.
[0028] <Inorganic fiber materials> The rubber composition according to the present disclosure contains an inorganic fiber material. The inorganic fiber material oriented in the tire circumferential direction imparts anisotropy to the strength and rigidity, thereby realizing a flexible response to input (vibration) from the vertical direction of the tire during rolling, and increasing the rigidity in the orientation direction (tire circumferential direction) improves the responsiveness to input during steering.
[0029] Inorganic fiber materials that can be used in the present disclosure are not particularly limited, but include, for example, magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, sepiolite, glass fiber, etc., and one or more inorganic fiber materials selected from the group consisting of magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, and sepiolite are preferred, and magnesium sulfate fiber is more preferred. The inorganic fiber materials may be used alone or in combination of two or more.
[0030] Magnesium sulfate fiber is MgSO4 5Mg(OH) 2 3H 2 The basic magnesium sulfate fiber represented by 6CaO 6SiO is preferred. 2 H 2 The calcium silicate fiber represented by K is preferred. The potassium titanate fiber represented by K 2 O 6TiO 2 or K 2 O 8TiO 2 As the aluminum borate fiber, 9Al 2 O 3 2B 2 O 3 As the sepiolite, Mg 8 S 12 O 30 (OH) 4 (H 2 O) 4 8H 2 Sepiolite represented by O is preferred.
[0031] The inorganic fiber material may be commercially available or may be manufactured by a known manufacturing method. Specific examples of the inorganic fiber material include inorganic fiber materials manufactured and sold by Ube Material Industries, Ltd., Otsuka Chemical Co., Ltd., Shikoku Chemical Industries, Ltd., Omi Mining Co., Ltd., etc.
[0032] The content of the inorganic fiber material per 100 parts by mass of the rubber component is preferably 1.0 part by mass or more, more preferably 1.5 parts by mass or more, even more preferably 2.0 parts by mass or more, and particularly preferably 2.5 parts by mass or more, from the viewpoint of the anisotropy of the rubber composition, and is preferably 50 parts by mass or less, more preferably 45 parts by mass or less, even more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less, from the viewpoint of the breaking strength of the rubber composition.
[0033] The average diameter D of the inorganic fiber material (also referred to as the average fiber diameter or average width) is preferably 1.0 nm or more, more preferably 2.0 nm or more, and even more preferably 3.0 nm or more from the viewpoint of the rigidity and processability of the rubber composition. Also, from the viewpoint of the rigidity and breaking strength of the rubber composition, it is preferably 2000 nm or less, more preferably 1000 nm or less, even more preferably 500 nm or less, and particularly preferably 100 nm or less.
[0034] The average length L of the inorganic fiber material (also referred to as the average fiber length) is preferably 0.10 μm or more, more preferably 0.15 μm or more, even more preferably 0.20 μm or more, and particularly preferably 0.50 μm or more from the viewpoint of the anisotropy of the rubber composition. Also, from the viewpoint of the rigidity and breaking strength of the rubber composition, it is preferably 100 μm or less, more preferably 80 μm or less, even more preferably 60 μm or less, and particularly preferably 40 μm or less.
[0035] In the present disclosure, the average diameter D and the average length L can be measured by image analysis of scanning electron micrographs, image analysis of transmission electron micrographs, analysis of X-ray scattering data, pore electrical resistance method (Coulter principle method), or the like.
[0036] From the viewpoint of anisotropy of the rubber composition, the aspect ratio L / D of the inorganic fiber material is preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, and particularly preferably 8 or more. From the viewpoint of the breaking strength of the rubber composition, the aspect ratio L / D is preferably 1000 or less, more preferably 500 or less, even more preferably 250 or less, and particularly preferably 100 or less.
[0037] <Coupling Agent> The rubber composition according to the present disclosure contains a coupling agent. Inorganic fiber materials are less likely to disperse in rubber components than fillers such as carbon black, but the incorporation of a coupling agent improves the dispersibility of the inorganic fiber materials and also improves anisotropy.
[0038] Coupling agents that can be used in the present disclosure include, but are not limited to, silane coupling agents that bond with silica and rubber components, carbon coupling agents that bond with carbon black and rubber components, and the like.
[0039] (Silane coupling agent) The silane coupling agent is not particularly limited, and any silane coupling agent conventionally used in combination with silica in the rubber industry can be used, and examples thereof include the following mercapto group-containing silane coupling agents; sulfide group-containing silane coupling agents such as bis(3-triethoxysilylpropyl) disulfide and bis(3-triethoxysilylpropyl) tetrasulfide; vinyl group-containing silane coupling agents such as vinyltriethoxysilane and vinyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-(2-aminoethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based silane coupling agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Among them, a silane coupling agent having a sulfide group and / or a silane coupling agent having a mercapto group is preferred, and a silane coupling agent having a sulfide group is more preferred. These silane coupling agents may be used alone or in combination of two or more.
[0040] The silane coupling agent having a mercapto group is preferably a compound represented by the following formula (1) and / or a compound containing a bonding unit A represented by the following formula (2) and a bonding unit B represented by the following formula (3). [ka] (In the formula, R 101 , R102 , and R 103 are each independently an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or -O-(R 111 -O) z -R 112 (z R 111 each independently represents a divalent hydrocarbon group having 1 to 30 carbon atoms; R 112 represents an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an aralkyl group having 7 to 30 carbon atoms; z represents an integer of 1 to 30; 104 represents an alkylene having 1 to 6 carbon atoms. [ka] [ka] (wherein x represents an integer of 0 or more; y represents an integer of 1 or more; R 201 represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, or an alkynyl group having 2 to 30 carbon atoms, which may be substituted by a hydroxyl or carboxyl group; R 202 represents an alkylene having 1 to 30 carbon atoms, an alkenylene having 2 to 30 carbon atoms, or an alkynylene having 2 to 30 carbon atoms; 201 and R 202 may form a ring structure.)
[0041] Examples of the compound represented by formula (1) include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and the compound represented by the following chemical formula (4) (Si363 manufactured by Evonik Degussa), and the compound represented by the following chemical formula (4) can be preferably used. These may be used alone or in combination of two or more. [ka]
[0042] Examples of compounds containing a bond unit A represented by formula (2) and a bond unit B represented by formula (3) include those manufactured and sold by Momentive, Inc. These may be used alone or in combination of two or more.
[0043] (Carbon coupling agent) The carbon coupling agent is not particularly limited, but includes tetrasulfide compounds such as bis(dimethylaminoethyl)tetrasulfide (DME) and bis(dimethylaminopropyl)tetrasulfide (DMP); benzimidazole compounds such as 1,2-bis(benzimidazolyl-2)ethane (EBZ) and 1,4'-bis(mercaptobenzimidazolyl-2)butane (C4SBZ); pyrithione metal salts, etc. These carbon coupling agents may be used alone or in combination of two or more.
[0044] The content of the coupling agent (preferably a silane coupling agent) per 100 parts by mass of the rubber component is preferably 1.0 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2.0 parts by mass or more from the viewpoint of improving the dispersibility of the inorganic fiber material, and is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and particularly preferably 15 parts by mass or less from the viewpoint of breaking strength.
[0045] When the content of the inorganic fiber material relative to 100 parts by mass of the rubber component is A (parts by mass), the content of the silica is B (parts by mass), and the content of the coupling agent (preferably a silane coupling agent) is X (parts by mass), it is preferable that A, B, and X satisfy the following formula (5). 0.09A+0.08B≦X≦0.35A+0.08B (5)
[0046] <Filling agent> The rubber composition may contain fillers that have been generally used in the rubber industry, such as carbon black, silica, aluminum hydroxide, calcium carbonate, alumina, clay, talc, etc. Of these, it is preferable to contain carbon black, and it is more preferable to contain carbon black and silica.
[0047] Carbon black has a high heat generation during mixing, which is thought to promote plasticization during mixing and to make it easier for inorganic fiber materials to react with coupling agents and disperse in the rubber matrix. At the same time, unlike inorganic fiber materials, it can provide a reinforcing effect without anisotropy, making it possible to impart the minimum necessary breaking strength in the anti-grain direction of the inorganic fibers. On the other hand, silica has a weaker reinforcing effect than carbon black and inorganic fiber materials, but it can provide supple reinforcement, which is thought to make it possible to reinforce the entire rubber matrix while maintaining flexibility in the anti-grain direction.
[0048] (Carbon Black) The carbon black is not particularly limited, and GPF, FEF, HAF, ISAF, SAF, and other carbon blacks commonly used in the tire industry can be used. Specifically, N110, N115, N120, N125, N134, N135, N219, N220, N231, N234, N293, N299, N326, N330, N339, N343, N347, N351, N356, N358, N375, N539, N550, N582, N630, N642, N650, N660, N683, N754, N762, N765, N772, N774, N787, N907, N908, N990, N991, and the like can be suitably used. In addition to these, in-house synthesized products and the like can also be suitably used. These carbon blacks may be used alone or in combination of two or more.
[0049] The nitrogen adsorption specific surface area of carbon black (N 2 SA) is a 30m long steel structure with a view to weather resistance and reinforcement. 2 / g or more is preferable, and 35m 2 / g or more is more preferable, and 40m 2 From the viewpoints of dispersibility, fuel efficiency, breakage characteristics and durability, it is more preferable that the content is 250 m 2 / g or less is preferable, and 220m 2 In this specification, the N 2 SA is a value measured in accordance with Method A of JIS K 6217-2:2017 "Carbon black for rubber - Basic characteristics - Part 2: Determination of specific surface area - Nitrogen adsorption method - Single point method."
[0050] The cetyltrimethylammonium bromide adsorption specific surface area (CTAB) of the carbon black is set to 180 m from the viewpoint of preventing the rubber network from becoming excessively strong and ensuring the anisotropy of the rubber composition. 2 / g or less is preferable, and 165m 2 / g or less is more preferable, and 150m 2 On the other hand, the lower limit of the CTAB of carbon black is not particularly limited, but from the viewpoint of reinforcing properties, it is preferably 30 m 2 / g or more is preferable, and 40m 2 / g or more is more preferable, and 50m 2 / g or more is more preferable. Here, CTAB is a value correlated with the particle size of carbon black, and the larger CTAB is, the smaller the particle size of carbon black is. Note that the CTAB of carbon black in this specification is a value measured in accordance with JIS K 6217-3:2001 "Carbon black for rubber-Fundamental properties-Part 3: Determination of specific surface area-CTAB adsorption method".
[0051] When carbon black is contained, the content per 100 parts by mass of the rubber component is preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, and particularly preferably 15 parts by mass or more, from the viewpoint of weather resistance and reinforcement, and is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 60 parts by mass or less, from the viewpoint of fuel economy.
[0052] (silica) The silica is not particularly limited, and can be, for example, silica prepared by a dry method (anhydrous silica), silica prepared by a wet method (hydrated silica), or other silica commonly used in the tire industry. Among them, hydrated silica prepared by a wet method is preferred because it contains a large number of silanol groups. These silicas can be used alone or in combination of two or more.
[0053] The nitrogen adsorption specific surface area of silica (N 2 SA) is a 140m 2 / g or more is preferable, and 150m 2 / g or more is more preferable, and 160m 2 / g or more is more preferable, and 170m 2 From the viewpoints of fuel economy and processability, it is particularly preferable that the tensile strength is 350 m 2 / g or less is preferable, and 300m 2 / g or less is more preferable, and 250m 2 / g or less is more preferable. 2 SA is a value measured by the BET method in accordance with ASTM D3037-93.
[0054] When silica is contained, the content per 100 parts by mass of the rubber component is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and particularly preferably 20 parts by mass or more from the viewpoint of fuel efficiency performance, and is preferably 110 parts by mass or less, more preferably 100 parts by mass or less, even more preferably 90 parts by mass or less, and particularly preferably 80 parts by mass or less from the viewpoint of processability.
[0055] The total content of silica and carbon black per 100 parts by mass of the rubber component is preferably 20 parts by mass or more, more preferably 25 parts by mass or more, even more preferably 30 parts by mass or more, and particularly preferably 35 parts by mass or more, from the viewpoint of reinforcement, and is preferably 200 parts by mass or less, more preferably 170 parts by mass or less, even more preferably 150 parts by mass or less, and particularly preferably 130 parts by mass or less, from the viewpoint of processability.
[0056] The content of silica in the total content of silica and carbon black is preferably 50% or more, more preferably 70% or more, and even more preferably 80% or more.
[0057] The content of the inorganic fiber material in the total content of the inorganic fiber material, silica, and carbon black is preferably 5% by mass or more, and more preferably 8% by mass or more. This makes it easier to obtain the anisotropic effect of the inorganic fiber material. On the other hand, the content of the inorganic fiber material in the total content of the inorganic fiber material, silica, and carbon black is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. This makes it possible to reinforce the rubber phase only in the grain direction and prevent the strength from becoming extremely weak in the anti-grain direction.
[0058] <Other compounding agents> In addition to the above components, the rubber composition may appropriately contain compounding agents commonly used in the tire industry, such as plasticizers, waxes, antioxidants, vulcanizing agents such as stearic acid, zinc oxide, and sulfur, vulcanization accelerators, etc., and it is preferable to contain a plasticizer. By containing a plasticizer, the viscosity of the rubber is reduced during mixing, making it easier to disperse the inorganic fiber material, which tends to improve the anisotropy and breaking strength. Examples of plasticizers include oils, resin components, and liquid rubbers.
[0059] Examples of the oil include aromatic oil, process oil, mineral oil such as paraffin oil, etc. Among them, it is preferable to use process oil because of the reduction of the burden on the environment.
[0060] When oil is contained, the content per 100 parts by mass of the rubber component is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, from the viewpoint of processability. Also, from the viewpoint of abrasion resistance, the content is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, and particularly preferably 50 parts by mass or less. In this specification, the content of oil includes the amount of oil contained in the oil-extended rubber.
[0061] The resin component is not particularly limited, but examples thereof include petroleum resins, terpene resins, rosin resins, phenolic resins, etc. commonly used in the tire industry. Examples of petroleum resins include C5 petroleum resins, aromatic petroleum resins, C5C9 petroleum resins, etc. These resin components may be used alone or in combination of two or more.
[0062] In this specification, the term "C5 petroleum resin" refers to a resin obtained by polymerizing a C5 fraction. Examples of C5 fractions include petroleum fractions having 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. As the C5 petroleum resin, dicyclopentadiene resin (DCPD resin) is preferably used.
[0063] In this specification, the term "aromatic petroleum resin" refers to a resin obtained by polymerizing a C9 fraction, and may be a hydrogenated or modified resin. Examples of C9 fractions include petroleum fractions having 8 to 10 carbon atoms, such as vinyl toluene, alkyl styrene, indene, and methyl indene. Specific examples of aromatic petroleum resins include, for example, Coumarone-indene resin, coumaron resin, indene resin, and aromatic vinyl resin are preferably used. As the aromatic vinyl resin, a homopolymer of α-methylstyrene or styrene, or a copolymer of α-methylstyrene and styrene is preferred, and a copolymer of α-methylstyrene and styrene is more preferred, because they are economical, easy to process, and have excellent heat generation properties. As the aromatic vinyl resin, for example, commercially available products from Kraton, Eastman Chemical, etc. can be used.
[0064] In this specification, the term "C5C9 petroleum resin" refers to a resin obtained by copolymerizing the C5 fraction and the C9 fraction, and may be a hydrogenated or modified resin. Examples of the C5 fraction and the C9 fraction include the petroleum fractions described above. As the C5C9 petroleum resin, for example, those commercially available from Tosoh Corporation, LUHUA, etc. can be used.
[0065] Examples of the terpene resin include polyterpene resins consisting of at least one selected from terpene compounds such as α-pinene, β-pinene, limonene, and dipentene; aromatic modified terpene resins made from the terpene compounds and aromatic compounds; terpene phenolic resins made from terpene compounds and phenolic compounds; and terpene resins obtained by subjecting these terpene resins to hydrogenation treatment (hydrogenated terpene resins). Examples of aromatic compounds that are raw materials for aromatic modified terpene resins include styrene, α-methylstyrene, vinyltoluene, and divinyltoluene. Examples of phenolic compounds that are raw materials for terpene phenolic resins include phenol, bisphenol A, cresol, and xylenol.
[0066] The rosin-based resin is not particularly limited, but examples thereof include natural resin rosin and rosin-modified resins obtained by modifying rosin by hydrogenation, disproportionation, dimerization, esterification, or the like.
[0067] The phenol-based resin is not particularly limited, but examples thereof include phenol formaldehyde resin, alkylphenol formaldehyde resin, alkylphenol acetylene resin, and oil-modified phenol formaldehyde resin.
[0068] When a resin component is contained, the content thereof per 100 parts by mass of the rubber component is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more. The content of the resin component is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less.
[0069] The liquid rubber is not particularly limited as long as it is a polymer that is in a liquid state at room temperature (25° C.), and examples thereof include liquid butadiene rubber (liquid BR), liquid styrene butadiene rubber (liquid SBR), liquid isoprene rubber (liquid IR), liquid styrene isoprene rubber (liquid SIR), liquid farnesene rubber, etc. These liquid rubbers may be used alone or in combination of two or more kinds.
[0070] When the liquid rubber is contained, the content per 100 parts by mass of the rubber component is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more. The content of the liquid rubber is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less.
[0071] The content of the plasticizer per 100 parts by mass of the rubber component (when multiple plasticizers are used in combination, the total amount of all of them) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more. The content of the plasticizer is preferably 90 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 50 parts by mass or less, and particularly preferably 30 parts by mass or less. If the content of the plasticizer exceeds 90 parts by mass, the plasticizer causes softening of the entire rubber matrix, and sufficient reinforcement by the inorganic fiber material cannot be obtained, so that anisotropy and breaking strength tend to decrease.
[0072] When the wax is contained, the content thereof per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more from the viewpoint of weather resistance of the rubber, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less from the viewpoint of preventing whitening of the tire due to bloom.
[0073] The antiaging agent is not particularly limited, and examples thereof include amine-based, quinoline-based, quinone-based, phenol-based, and imidazole-based compounds, and carbamic acid metal salts. Examples of the antiaging agent include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, N-cyclohexyl-N'-phenyl-p-phenylenediamine, N,N'-bis(1-methylheptyl)-p-phenylenediamine, N,N'-bis(1,4-dimethyl Preferred are phenylenediamine-based antioxidants such as N,N'-bis(1-ethyl-3-methylpentyl)-p-phenylenediamine, N-4-methyl-2-pentyl-N'-phenyl-p-phenylenediamine, N,N'-diaryl-p-phenylenediamine, hindered diaryl-p-phenylenediamine, phenylhexyl-p-phenylenediamine, and phenyloctyl-p-phenylenediamine, and quinoline-based antioxidants such as 2,2,4-trimethyl-1,2-dihydroquinoline polymer and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline. These antioxidants may be used alone or in combination of two or more.
[0074] When an antioxidant is contained, the content per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more from the viewpoint of ozone crack resistance of the rubber, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less from the viewpoint of abrasion resistance and wet grip performance.
[0075] When stearic acid is contained, the content per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more from the viewpoint of processability, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less from the viewpoint of vulcanization speed.
[0076] When zinc oxide is contained, the content per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more from the viewpoint of processability, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less from the viewpoint of abrasion resistance.
[0077] As the vulcanizing agent, sulfur is preferably used, and examples of the sulfur that can be used include powdered sulfur, oil-treated sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, and highly dispersible sulfur.
[0078] When sulfur is contained as a vulcanizing agent, the content per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, from the viewpoint of ensuring sufficient vulcanization reaction and obtaining good grip performance and abrasion resistance, and is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4.0 parts by mass or less, from the viewpoint of preventing deterioration.
[0079] Examples of vulcanizing agents other than sulfur include vulcanizing agents containing sulfur atoms, such as TACKIROL V-200 manufactured by Taoka Chemical Co., Ltd., DURALINK HTS (sodium 1,6-hexamethylenedithiosulfate dihydrate) manufactured by Flexis, and KA9188 (1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane) manufactured by LANXESS K.K., as well as organic peroxides such as dicumyl peroxide.
[0080] The vulcanization accelerator is not particularly limited, but examples thereof include sulfenamide-based, thiazole-based, thiuram-based, thiourea-based, guanidine-based, dithiocarbamic acid-based, aldehyde-amine-based or aldehyde-ammonia-based, imidazoline-based, and xanthate-based vulcanization accelerators. Among these, sulfenamide-based and guanidine-based vulcanization accelerators are preferred because they more suitably achieve the desired effects, and it is more preferable to use these two types in combination.
[0081] Examples of sulfenamide vulcanization accelerators include CBS (N-cyclohexyl-2-benzothiazolyl sulfenamide), TBBS (Nt-butyl-2-benzothiazolyl sulfenamide), N-oxyethylene-2-benzothiazolyl sulfenamide, N,N'-diisopropyl-2-benzothiazolyl sulfenamide, and N,N-dicyclohexyl-2-benzothiazolyl sulfenamide. Examples of thiazole vulcanization accelerators include 2-mercaptobenzothiazole and dibenzothiazolyl disulfide. Examples of thiuram vulcanization accelerators include tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and tetrabenzylthiuram disulfide (TBzTD). Examples of guanidine vulcanization accelerators include 1,3-diphenylguanidine (DPG), di-orthotolyl guanidine, and orthotolyl biguanidine. These vulcanization accelerators may be used alone or in combination of two or more kinds.
[0082] When a vulcanization accelerator is contained, the content per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more. The content per 100 parts by mass of the rubber component is preferably 8 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 6 parts by mass or less. By setting the content of the vulcanization accelerator within the above range, breaking strength and elongation tend to be secured.
[0083] [Method of manufacturing rubber composition and tire] The rubber composition of the present disclosure can be produced by a known method, for example, by kneading the components other than the vulcanizing agent and vulcanization accelerator among the above-mentioned components in a known kneading machine generally used in the rubber industry, such as a Banbury mixer, a kneader, or an open roll, adding the vulcanizing agent and the vulcanization accelerator to the kneaded mixture, further kneading the mixture, and then vulcanizing the mixture. For example, in the kneading step, the mixture is kneaded at 80°C to 170°C for 1 minute to 30 minutes, and in the vulcanization step, the mixture is vulcanized at 130°C to 190°C for 3 minutes to 20 minutes.
[0084] The rubber composition of the present disclosure realizes a supple response to input (vibration) from the tire vertical direction during rolling by orienting the inorganic fibers in the tire circumferential direction, and is considered to improve the responsiveness to the input during steering by increasing the rigidity in the orientation direction (tire circumferential direction). For this reason, it can be suitably used for components that are continuous in the tire circumferential direction, such as cap tread, base tread, sidewall, sidewall inner layer, inner liner, strip apex, bead apex, clinch apex, bead reinforcing layer, insulation, and insert, and it is considered that the same effect can be obtained in any of them. In particular, it is suitable for use as a rubber composition for tire internal components, such as base tread, sidewall inner layer, inner liner, strip apex, bead apex, bead reinforcing layer, insulation, and insert. By using the rubber composition of the present disclosure as such a tire internal component, it is possible to improve the elasticity (responsiveness) of the tire in the rolling direction while maintaining cushioning properties, and therefore it is considered that the steering stability and ride comfort are improved.
[0085] In this specification, the term "internal components" is not limited to the above-mentioned components, but refers to tire components other than those that form the outer surface when the tire is mounted on a rim and filled with air.
[0086] The tire of the present disclosure can be manufactured by a normal method using the rubber composition. That is, an unvulcanized rubber composition in which the above-mentioned components are mixed with the rubber component as necessary is extruded according to the shape of the corresponding tire component to obtain a rubber composition in which the inorganic fiber material is oriented in the grain direction. Then, the rubber composition is laminated with other tire components on a tire building machine so that the inorganic fiber material is oriented in the tire circumferential direction, and molded by a normal method to form an unvulcanized tire, and the unvulcanized tire is heated and pressurized in a vulcanizer to manufacture a tire. The tire of the present disclosure can be a pneumatic tire or a non-pneumatic tire. In addition, it is suitable for racing tires, passenger car tires, large passenger car tires, large SUV tires, and motorcycle tires, and can be used as summer tires, winter tires, and studless tires for each. EXAMPLES
[0087] The present disclosure will be described based on examples, but the present disclosure is not limited to only the examples.
[0088] The various chemicals used in the examples and comparative examples are listed below. NR:TSR20 BR: Ubepol BR150B (cis content: 97%) from Ube Industries, Ltd. SBR1: Tufuden 3830 manufactured by Asahi Kasei Corporation (unmodified S-SBR, styrene content: 32% by mass, oil-extended product containing 37.5 parts by mass of oil per 100 parts by weight of rubber component) SBR2: Asaprene 1205 manufactured by Asahi Kasei Corporation (unmodified S-SBR, styrene content: 25% by mass) Carbon black: Cabot Japan Co., Ltd. Show Black N220 (CTAB: 110m 2 / g, N 2 SA:111m 2 / g) Silica: ULTRASIL® VN3 (N) manufactured by Evonik Degussa 2 SA: 175m 2 / g) Inorganic fiber material 1: Mos-Hige manufactured by Ube Material Industries, Ltd. (basic magnesium sulfate fiber, average fiber diameter: 500 to 1000 nm, average fiber length: 8 to 30 μm) Inorganic fiber material 2: Sepiolite (average fiber diameter: 5 to 30 nm, average fiber length: 0.2 to 2.0 μm) Inorganic fiber material 3: Zonohygi manufactured by Ube Material Industries, Ltd. (calcium silicate fiber, average fiber diameter: 100 to 500 nm, average fiber length: 1 to 5 μm) Silane coupling agent: Si69 (bis(3-triethoxysilylpropyl)tetrasulfide) manufactured by Evonik Degussa Oil: Process oil X-140 manufactured by ENEOS Corporation Anti-aging agent: Ozonone 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Seiko Chemical Co., Ltd. Stearic acid: NOF Corporation's "Tsubaki" stearic acid Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining & Smelting Co., Ltd. Wax: Ozoace 0355 manufactured by Nippon Seiro Co., Ltd. Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Vulcanization accelerator 1: Soxinol CZ (N-cyclohexyl-2-benzothiazolyl sulfenamide) manufactured by Sumitomo Chemical Co., Ltd. Vulcanization accelerator 2: Soxinol D (1,3-diphenylguanidine) manufactured by Sumitomo Chemical Co., Ltd.
[0089] Examples and Comparative Examples According to the compounding recipes shown in Tables 1 and 2, materials other than sulfur and vulcanization accelerator were kneaded using a Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the obtained kneaded product, and the mixture was kneaded using an open roll to obtain an unvulcanized rubber composition. A sheet having a thickness of 0.5 mm was produced from the obtained unvulcanized rubber composition using an open roll. The obtained unvulcanized rubber sheets were stacked to form a sheet having a thickness of 1.5 mm, and press-vulcanized at 150°C for 15 minutes to produce a vulcanized rubber sheet for testing. The unvulcanized rubber composition was extruded to match the shape of the sidewall inner layer using an extruder equipped with a die of a predetermined shape, to obtain a sidewall inner layer in which the inorganic fiber material is oriented in the grain direction. The sidewall inner layer was then bonded together with other tire components on a tire building machine so that the inorganic fiber material was oriented in the tire circumferential direction to form an unvulcanized tire, and a tire (size: 205 / 65R15) was manufactured by press-vulcanizing the tire for 12 minutes under conditions of 170°C.
[0090] <Anisotropy test> From the vulcanized rubber sheet, a JIS No. 3 dumbbell was used to punch out in the grain direction (the direction of roll rotation when manufacturing the unvulcanized rubber sheet before vulcanization), and the tensile stress (M100a) at 100% elongation in the grain direction was measured under the condition of a tensile speed of 500 mm / min in accordance with JIS K 6251: 2017. Similarly, a JIS No. 3 dumbbell was used to punch out in the anti-grain direction (perpendicular to the direction of roll rotation when manufacturing the unvulcanized rubber sheet before vulcanization), and the tensile stress (M100b) at 100% elongation in the anti-grain direction was measured under the condition of a tensile speed of 500 mm / min in accordance with JIS K 6251: 2017. The calculated modulus ratios (M100a / M100b) are shown in Tables 1 and 2.
[0091] <Tensile test> Using a No. 3 dumbbell-shaped test piece made of a vulcanized rubber composition, the elongation at break EB (%) and tensile strength at break TB (MPa) of the vulcanized rubber sheet were measured in accordance with JIS K 6251:2017. From the obtained values, the breaking strength was calculated using the following formula, and expressed as an index (breaking strength index) with the reference comparative example (Comparative Example 1 in Table 1, Comparative Example 3 in Table 2; the same applies below) taken as 100. A larger index indicates better breaking strength. Breaking strength = EB × TB / 2
[0092] <Evaluation of steering stability and ride comfort> The prototype tire was mounted on a standard rim (size = 16 x 6.5J) and filled with air to an internal pressure of 210 kPa. This tire was mounted on a car with an engine displacement of 2000 cc. The car was driven on a test course with an asphalt road surface, and a test driver performed a sensory evaluation of the ride comfort and the stability of control during steering (handling stability). The evaluation was performed on a scale of 10 points, with the standard comparative example being 6.0 points, and a relative evaluation was performed. A higher score indicates better handling stability and ride comfort.
[0093] [Table 1]
[0094] [Table 2]
[0095] The results in Tables 1 and 2 show that the rubber composition of the present disclosure, which contains an inorganic fiber material and a coupling agent, can achieve high levels of both fracture strength and anisotropy. Also, the tire of the present disclosure, which includes an internal tire component made of the rubber composition, has a well-balanced improvement in ride comfort and handling stability.
Claims
1. A rubber composition comprising a rubber component, an inorganic fiber material, carbon black, and a coupling agent, the inorganic fiber material is one or more inorganic fiber materials selected from the group consisting of magnesium sulfate fiber, calcium silicate fiber, aluminum borate fiber, and glass fiber; The inorganic fiber material is contained in an amount of 1 to 50 parts by mass per 100 parts by mass of the rubber component, The inorganic fiber material has an average diameter D of 1.0 to 2000 nm, an average length L of 0.10 to 100 μm, and an aspect ratio L / D of 2 to 1000; The rubber composition has a carbon black content of 30 parts by mass or more based on 100 parts by mass of the rubber component.
2. A rubber composition comprising a rubber component, an inorganic fiber material, carbon black, and a coupling agent, the inorganic fiber material is one or more inorganic fiber materials selected from the group consisting of magnesium sulfate fiber, calcium silicate fiber, aluminum borate fiber, and glass fiber; The inorganic fiber material is contained in an amount of 1 to 50 parts by mass per 100 parts by mass of the rubber component, The inorganic fiber material has an average diameter D of 1.0 to 2000 nm, an average length L of 0.10 to 100 μm, and an aspect ratio L / D of 2 to 1000; The rubber component contains 5% by mass or more of butadiene rubber, The rubber composition has a carbon black content of 30 parts by mass or more based on 100 parts by mass of the rubber component.
3. 3. The rubber composition according to claim 2, wherein the ratio (M100a / M100b) of the 100% modulus M100a in the grain direction to the 100% modulus M100b in the anti-grain direction is 1.10 or more.
4. A rubber composition comprising a rubber component, an inorganic fiber material, carbon black, and a coupling agent, the inorganic fiber material is one or more inorganic fiber materials selected from the group consisting of magnesium sulfate fiber, calcium silicate fiber, aluminum borate fiber, and glass fiber; The inorganic fiber material is contained in an amount of 1 to 50 parts by mass per 100 parts by mass of the rubber component, The inorganic fiber material has an average diameter D of 1.0 to 2000 nm, an average length L of 0.10 to 100 μm, and an aspect ratio L / D of 2 to 1000; The amount of carbon black per 100 parts by mass of the rubber component is 30 parts by mass or more, A rubber composition having a ratio (M100a / M100b) of 100% modulus M100a in the grain direction to 100% modulus M100b in the anti-grain direction of 1.10 or more.
5. The rubber composition according to any one of claims 1 to 4, further comprising a plasticizer.
6. The rubber composition according to any one of claims 1 to 5, wherein the rubber component comprises an isoprene-based rubber.
7. The rubber composition according to any one of claims 1 to 6, wherein the coupling agent is a silane coupling agent.
8. The rubber composition according to any one of claims 1 to 7, comprising 1 to 40 parts by mass of the coupling agent per 100 parts by mass of the rubber component.
9. The rubber composition according to any one of claims 1 to 8, wherein the coupling agent is a silane coupling agent having a sulfide group.
10. Furthermore, the cetyltrimethylammonium bromide adsorption specific surface area (CTAB) is 180m 2 The rubber composition according to any one of claims 1 to 9, further comprising carbon black having a molecular weight of 1 / g or less.
11. The rubber composition according to any one of claims 1 to 10, wherein the inorganic fiber material is one or more inorganic fiber materials selected from the group consisting of magnesium sulfate fibers, calcium silicate fibers, and aluminum borate fibers.
12. A tire using the rubber composition according to any one of claims 1 to 11 as a tire component.
13. 13. The tire of claim 12, wherein the tire is a passenger tire.
Citation Information
Patent Citations
Rubber composition, rubber composition for tread, and pneumatic tire
WO2020121788A1
Semiconductor device
JP1981091463A